Brazilian Nursing and Psychology students' visits to patients with amyotrophic lateral sclerosis: prospective analysis - Antonio Geraldo Abreu Filho; Leila Salomão Plata Cury Tardivo; Acary Souza Bulle Oliveira; Helga Cristina Almeida da Silva (Arquivos de Neuro-Psiquiatria)
ABSTRACT Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease without a cure, but multidisciplinary treatment can maintain the quality of life (QOL) of persons with ALS (PALS). Despite health professionals possibly being affected by ALS in their care roles, little is known about the impact of ALS care on these professionals. Objective: To analyze the effects of interactions between PALS and Nursing/Psychology students. Methods: Over 12 weeks, 16 student pairs performed weekly 60-minute home visits to 16 PALS. Instruments used for analyses were the McGill Quality of Life Questionnaire for the PALS; and the Draw-a-Person test and the Desiderative Questionnaire for the students. All instruments were applied twice: at the beginning (pre-first visit) and at the end of the study (post-12 visits). Results: After 12 weeks, there was not a significant change in total QOL or its five domains (existential wellbeing, physical wellbeing, psychological wellbeing, physical symptoms, and support). Existential wellbeing/support domains contributed most to the QOL of the PALS (pre-first visit and post-12 visits). Students showed anxiety/impulsivity but preserved adequacy to reality, logical thinking and global perception with regard to the PALS. We found that students were psychologically fragile in some subgroups/moments. Conclusions: Students' visits to PALS may contribute to the maintenance of the QOL of the patients. Additionally, visits, with psychological support for the students, seem safe and could contribute to the students' psychological maturation as health professionals. Additional psychological support may be necessary for some students in fragile subgroups/moments.